Creative Thinking in Different Countries' Modern Education Systems (Comparative Analyze) - Vafa Azad, Mirzazade (Педагогически форум, 2025)
The paper’s aim is to present the main ideas about creative thinking in various countries' modern education systems. The main goal of modern education is the development of the child's personality. This goal is achieved by humanizing the learning process and creating the potential for the child's fundamental development. To achieve this goal, integrated learning should be used. Integration processes in education are a rather complex and comprehensive concept, which requires analysis from a psychological and pedagogical point of view. The main goal of integrated learning is to ensure the intellectual development of students by creating a holistic picture of the world, therefore it is necessary to determine the psychophysiological foundations of knowledge, accurate ideas about the actual features of the development of basic thinking activities in childhood. The method of the research is comparative analysis of the literature materials, according to positivist methodology principles.